Theater, Childhood, Education - Roberto Farnè (University of Bologna, 2021)
Children love theater without knowing that they "do theater", without someone teaching them to "play a part": representing roles and situations is a spontaneous and natural playful dimension. We can call this "animation", a characteristic feature of childhood: in the proper sense it means "giving life" (movement, communication) by impersonating roles or creating scenarios with toys. Theater becomes a pedagogical device when it recognizes and enhances these assumptions by acting on two levels: on the one hand, making theater with children and young people, soliciting their communication and interpretative skills, as a laboratory that, starting from the body, involves all languages. On the other hand, making theater for children, producing shows able to enter a relationship with the imagination of children, as an aesthetic experience; at its best it is experimental theater.